2016
DOI: 10.2174/1573396312666160914193357
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse and Neglect and its Psycho-Physical and Social Consequences: A Review of the Literature

Abstract: Child maltreatment is a complex life experience occurs when a parent or caregiver does an intentional or potential damage to a child, including acts of commission and omission. Child abuse is not an uncommon event, but it is not always recognized. Identifying the real number of maltreated children is a challenge because of the large variability in reported prevalence data across studies. Unfortunately, in the United States, it affects 1 in 8 children, by the age of 18 years, annually. Paediatricians may encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…The present studies revealed that there are no common national guidelines in use by dentists in Norway, concordant with other European studies, which may lead to uncertainty and nonreporting (105,108,116,149,(151)(152)(153)(154)(155). Regarding child maltreatment, the GPs mainly referred to Norwegian legislation, and the GDPs referred to a local guideline.…”
Section: Resultssupporting
confidence: 85%
“…The present studies revealed that there are no common national guidelines in use by dentists in Norway, concordant with other European studies, which may lead to uncertainty and nonreporting (105,108,116,149,(151)(152)(153)(154)(155). Regarding child maltreatment, the GPs mainly referred to Norwegian legislation, and the GDPs referred to a local guideline.…”
Section: Resultssupporting
confidence: 85%
“…A relative consensus exists regarding the consequences of childhood maltreatment on emotional, behavioral, and social functioning during childhood and adolescence (Ferrara et al, 2016; Hunt, Slack, & Berger, 2016). Longitudinal studies have also shown that the negative impact of maltreatment may persist into adulthood and affect multiple domains of life, such as physical and mental health, intimate relationships, employment, and criminal offending (Herrenkohl, Hong, Klika, Herrenkohl, & Russo, 2013; Mersky & Topitzes, 2010; Smith, Ireland, & Thornberry, 2005).…”
mentioning
confidence: 99%
“…With proper education and training, most abuse can be prevented or interrupted 13 . Data of this study showed a statistically signi cant correlation between the number of training hours completed by respondents during their medical school and residency courses and those who believe they have su cient education on CAN (p 0.002).…”
Section: Discussionmentioning
confidence: 99%